Identification of autoantibodies to RNA polymerase II. Occurrence in systemic sclerosis and association with autoantibodies to RNA polymerases I and III. - Hirakata, M (1993)
In this study, autoantibodies to RNA polymerase II from sera of patients with systemic sclerosis have been identified and characterized. These antibodies immunoprecipitated polypeptides of 220 kD (IIA) and 145 kD (IIC), the two largest subunits of RNA polymerase II, and bound both subunits in immunoblots. These polypeptides were immunoprecipitated by the anti-RNA polymerase II monoclonal antibody 8WG16, which recognizes the carboxyl-terminal domain of the 220-kD subunit, and their identity to the proteins bound by human sera was confirmed in immunodepletion studies. Sera with anti-RNA polymerase II antibodies also immunoprecipitated proteins that were consistent with components of RNA polymerases I and III. In vitro transcription experiments showed that the human antibodies were an effective inhibitor of RNA polymerase II activity. In indirect immunofluorescence studies, anti-RNA polymerase II autoantibodies stained the nucleoplasm, as expected from the known location of RNA polymerase II, and colocalized with the anti-RNA polymerase II monoclonal antibody. The human sera also stained the nucleolus, the location of RNA polymerase I. From a clinical perspective, these antibodies were found in 13 of 278 patients with systemic sclerosis, including 10 with diffuse and three with limited cutaneous disease, but were not detected in sera from patients with other connective tissue diseases and from normal controls. We conclude that anti-RNA polymerase II antibodies are specific to patients with systemic sclerosis, and that they are apparently associated with antibodies to RNA polymerases I and III. These autoantibodies may be useful diagnostically and as a probe for further studies of the biological function of RNA polymerases.